A meteorological study of severe floods of August 1976 in Jammu & Kashmir (MAUSAM, 1987)
In this paper a meteorological study has been made of the severe floods that occurred in tow quick successions in Jammu & Kashmir State in the first two weeks of August 1976. Vortices, with tropical characteristics, formed independently over the State when deep incursion of moist southerlies took place from the Bay and the Arabian Sea due to northwestward movement of a depression followed by another well marked low over Rajasthan. These vortices gave heavy precipitation, which resulted in severe floods in the State.